The Force of Freedom - Oyedepo, David (Nigeria, 1996)
This book from the author is a determined, fervent, vehement war against ignorance in the church of Jesus Christ! His fierce teachings on the pursuit of knowledge have erupted into an enviable reading culture among his congregation...
Keywords: Christian Life; Non-Fiction; Religion